Decisional conflict among parents of children with congenital heart disease towards development of a nursing model - So, Iris Chua
Parents of children with congenital heart disease experience decisional conflict given the nature of their child’s condition and dilemma inherent in treatment decisions. This study aimed to develop a nursing model on decisional conflict that would guide nurses to assist parents cope with decisional conflict. Correlational design with model building and data triangulation was used. Thru consecutive sampling, participants included 221 adult parents whose child underwent cardiac surgery. Structural equation modeling and qualitative data analysis were used. Lower decisional conflict was seen in parents with higher income ( = -.23, = .004), more nurse support ( = -.19, =.008) and physician risk communication ( = -.55, = .004). Longer time delay for surgery was correlated with child’s age ( = -.46, = .004), Philhealth z-benefit or social service coverage ( = -.15, = .007), and social support ( = -.16, = .045). Decisional conflict mediated the influence of income ( = -.12, = .004), nurse support ( = -.11, = .008), and physician risk communication ( = -.30, = .004 & = -.20, = .027) on satisfaction with decision. Based on model fit parameters, the emerging model is a good and parsimonious model on decisional conflict. Mapping the process parents go through in making treatment decisions, the overall theme, “Deciding for Surgery: What Matters Most,” emerged. Three themes were further identified: (1) Weighing the Options, (2) Tipping the Scale, and (3) Standing by the Choice. Filling the gap in knowledge, consistency with personal values, availability of support, and access to resources are more likely to help parents feel more certain, less conflicted, and more satisfied with their decision. Parents with young children, government subsidized healthcare cost, and social support tend towards longer time delay for surgery.